Grammarly in students' self-directed learning for writing skills: Advantages and disadvantages - Astuti, Dwi; Sumarni, Sri (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2023)
Grammarly as an online grammar checker impacted technology development rapidly. This study aimed to look at the benefits and weaknesses of utilizing Grammarly to improve students' self-directed learning, particularly in writing skills. This study used a qualitative literature review. The data were collected from 10 relevant articles on Google Scholar with the keyword "Grammarly, self-directed Learning, and writing skills". The main issues addressed in this study were the benefits and the weaknesses of Grammarly in the period from 2018 to 2023. The result showed that Grammarly could enhance 'students' self-directed learning. It was because of the advantages offered by Grammarly that could check the correctness, clarity, engagement, delivery, plagiarism, and convenience. However the weaknesses of Grammarly; it needed the stability of electricity and an internet connection; it needed high-speed internet connectivity to access the complete feature; it was incomplete service of a free version, while it needed to pay to access the premium version. In conclusion, Grammarly enhanced the caliber of their work and inspired them to gauge their development. Therefore, Grammarly is recommended because it enhances 'students' self-directed learning in writing skills.